Association of Ultra Processed Food Consumption and Body Mass Index for Age among Elementary Students in Surabaya - Azizah Ajeng Pratiwi; Dian Novita Chandra; Helda Khusun (Amerta Nutrition, 2022)
Background: Childhood obesity became a major nutritional problem in the last decades and growing rapidly in many countries, including Indonesia. Processed food especially ultra-processed food (UPF) as part of NOVA classification had known to contain obesogenic nutrients which were high energy-dense, fatty, sugary, and salty may lead to higher body mass index-for-age (BAZ). Objective: The study aimed to assess the correlation between UPF and BAZ among school-age children 10-12 years old in Surabaya. Methods: A cross-sectional study and data collection were conducted in three public and private schools in Surabaya, East Java Indonesia from March-April 2020. Elementary students in the 4th and 5th grades were enrolled and 136 students were randomly selected as respondents. Weight and height measurements were obtained for calculating the BAZ, and UPF consumption was obtained by food frequency questionnaire. Structured questionnaires and physical activity questionnaires for children (PAQ-C) were used to assess socio-demographic status, physical activity level, energy intake, and sedentary screen time. ANOVA test was done for bivariate analysis and linear regression for multivariate analysis, all data analyzed used SPSS version 20. Results: The result found a mean of BAZ was 0.31 SD; 35.3% of respondents were in the 1st tercile of UPF consumption. Most of the respondents had inadequate TEI and low PAL. No significant association was found between UPF consumption and BAZ (p=0.217). Only physical activity that significant in multivariate analysis (p=0.032) Conclusion: It was necessary to distinguish the type of obesogenic and non-obesogenic UPF to get a clear correlation between UPF consumption and BAZ among school-age children.